OBSERVATIONS ON THE INDO-WEST PACIFIC PALICIDAE (CRUSTACEA : DECAPODA) WITH DESCRIPTIONS OF TWO NEW SUBFAMILIES, FOUR NEW GENERA AND SIX NEW SPECIES - Moosa, M. Kasim; Serene, Raoul (Marine Research in Indonesia, 1981)
Twelve species of Crustacea of the family Palicidae were collected from Indonesian waters. Together with two species from the Philippines and type specimens of Crossotonotus compressipes A. Milne Edwards, 18 73, are studied and Manella spinipes is used for comparison. Two new subfamilies, four new genera, and six new species are described and the type of Crossotonotus compressipes has been designated.